The Effect of a training program based on Felder-Silverman model on improving reflective practices of Muslim bin Yasar Middle School teachers in Riyadh - Al-Bariqi, Ahmad Ali; Al-Bdour, Ahmad Hasan (Journal of Educational and Psychological Sciences, 2023)
This research aimed to The effect of a training program based on Felder – Silverman Model on Improving Reflective Practices of Muslim bin Yasar Middle School Teachers, in order to fulfill the study objectives the researcher has used the semi-experimental approach through the one-group design, and The training program was implemented during (16) training sessions over (8) weeks, with two sessions per week, each training session lasting one hour. It included definitions of the dimensions and patterns of the Felder-Silverman model, and was supported by examples and activities. the research sample consisted of 15 teachers from Muslim bin Yasar Middle School in Riyadh. the study used the reflective practices questionnaire as a tool to collection data Before and after the program, and to analyze the quantitative data Using the T-test to determine the significance of the differences between the pre- and post-tests, and the Eta square to measure the effectiveness of the training program, and after the analyzing data by using the Wilcoxon test to calculate the differences between the scores of the pre and post application of the research tool, the following results were reached: there are statistically significant differences between the pre and post applications in favor of the post application for the training program based on Felder – Silverman Model on Improving Reflective Practices of Middle School Teachers in axes (planning, implementation, and evaluation). In light of the results, the researcher recommended benefiting from the training program based on the Felder-Silverman model in the fields of training and teaching. He also recommended that teachers apply students’ learning styles, make it available content through assignments, activities, enrichments, and evaluation, and include teachers in electronic preparation on the Madrasati platform, as suggested. Complementary studies on the subject by applying a similar study to primary and high school teachers.
Keywords: Teaching Practices; Learning Styles; Felder – Silverman Indicator; Teacher Traning